Pertarungan Ideologi Realisme Sosialis dan Feodalisme Religis dalam Novel Midah Simanis Bergigi Emas Karya Pramoedya Ananta Toer - Moh Muzakka (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2019)
Literary work is a means for authors to offer various ideologies to their readers. Through literature, the author can influence the views of life and or ideology of the reader. From the inter-group conflict that was built into the structure of literary works, the author can fight for the ideology he adheres to. This short article intends to uncover the ideological struggle in Pramoedya Ananta Toer's novel Midah Simanis Bergigi Emas using the analysis of Gramsci's hegemony. The analysis shows that the Midah Simanis Bergigi Emas novel offers three ideologies namely the ideology of feudalism (which controls), the primitive ideology of coastal culture (which is mastered), and the ideology of socialist realism (which is championed). Because in the novel the two contrasting cultures are seen as bad culture, the culture of socialist realism is the most ideal.